Small power and its value in regional systems of the future - Bilodid V.D.; Taranets K. V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
This article deals with necessity of implementation of small energy powers in the electricity transmission system of Ukraine. There was made technical and economic estimation of technologies diversification. There were also outlined the main problems of the innovation market in dispersed energy and the variants of their solution are given.